Cyberbullies in Twitter: A focused review - Tsapatsoulis, Nicolas; Anastasopoulou, Vasiliki (My University, 2019)
This literature review focuses on recent techniques and studies regarding cyberbullying on Twitter. The purpose of these studies is to find smart and sophisticated ways and methods to detect these cyberbullying incidents and in case that it is not possible to fully eliminate them to provide the means to vastly reduce them. We present the theoretical roots of the term cyberbullying and we discuss thoroughly some influential studies to motivate new researchers that work in the general area of cybersecurity and privacy.
Keywords: Cyberbullying; Cybersecurity; Hashtags; Online media; Privacy; Twitter